CHANGES IN HEALTH AND HEALTH BEHAVIOURS DURING RETIREMENT TRANSITION BY SOCIOECONOMIC STATUS. (11th November 2018) - Stenholm, S; Halonen, J; Oksanen, T; Pentti, J; Kivimäki, M; Vahtera, J
Abstract: We examined whether and how changes in health and health behaviours during retirement transition are modified by individual and neighbourhood socioeconomic statuses (SES). The study population consisted of 9, 702 public-sector employees in the Finnish Public Sector study who retired in 2000–2011 and who reported their health and health behaviours pre- and post-retirement. Low occupational status was associated with greater decrease in poor self-rated health, but no difference was observed by neighbourhood SES. Of the health behaviours, physical activity increased most among people in the high occupational status and who lived in the most wealthy neighbourhoods. While people in the lower SES seem to benefit most in terms of health perception, positive changes in health behaviours, especially in physical activity, are seen mostly among high SES people.